Laser Cleaning‐Assisted Femtosecond Laser Direct Writing of Diamond Antireflective Microstructures with Superhigh Transmittance of 94.5% at 10.6 μm - He Cao; Yun‐Fei Li; Gong Wang; Hong‐Yu Li; De‐Rong Sun; Zi‐Qi Tang; Li‐Fang Li; Zhong‐Shan Jin; Yu Yu; Xue‐Qing Liu; Yu‐Lei Wang; Zhi‐Wei Lv; et al. (Small Structures)
Diamond‐based subwavelength antireflective microstructures are corrosion resistant, impact resistant, and possess high transmittance, thereby presenting broad application prospects in special optical windows. Nevertheless, fabricating uniform and highly transmissive subwavelength antireflective microstructures on diamond surfaces poses a significant challenge. The hard and brittle properties of diamond result in a large number of chips and particles, adhering to the surfaces during processing, which subsequently impacts the subsequent processing. Herein, a laser cleaning‐assisted femtosecond laser direct‐write processing technology is reported for fabricating subwavelength antireflective microstructures on diamond. To effectively avert the effects of chip accumulation, an elliptical laser spot is employed to clear the chips and polish the microstructure surface. The resulting highquality midinfrared antireflective microstructures are fabricated on diamond, and high transmittance (94.5%, with a 24.4% increase at 10 μm) within a broadband range (10–12 μm) is obtained, which represents the best results without antireflective coatings to the best of knowledge. Moreover, the antireflective structure possesses no significant angular dependence and maintains good working efficiency even at high temperature.